First record of the genus Parandes Muir, 1925 from China with descriptions of two new species (Hemiptera, Fulgoromorpha, Cixiidae) - Wang, Xiao-Ya; Zhi, Yan; Yang, Lin; Long, Jian-Kun; Chang, Zhi-Min; Chen, Xiang-Sheng (European Journal of Taxonomy, 2023)
The genus Parandes Muir, 1925 (Cixiinae, Andini) is recorded from China for the first time with two new species, Parandes circinatus Wang & Chen sp. nov. and Parandes fuscus Wang & Chen sp. nov. Color images for the adults of the two new species and line drawings for the genitalia are provided. A key is presented to separate all species within the genus.